Museum celebtates women's suffrage (Raton, NM Raton Range, 1996)
This article is about honoring National Women's History Month and the special exhibit displayed at the Raton Museum.
Newspaper article + Photograph of a Poster placed int he window of women who first registered to vote in 1921.
Master list item #: 50
File location is in the Raton file Cabinet
Keywords: Otero-Warren, Nina; Blanche, Deborah; Russeell, Marion Sloan; Raton Museum; Bank of New Mexico; K-Bob's Steakhouse; Museum Exhibits; National Women's History Month; Time Line Chronicle; Women's Rights; Women's Suffrage; Women's Hardships; Brown Bag Lunch Presentations; Raton, New Mexico; 216 South First Street